The effect of short-term alcohol restriction on risk of alcohol-related injury: A state wide population-based study. - Liang, Wenbin; Gilmore, W.; Chikritzhs, T. (2015)
BACKGROUND: Alcohol consumption and related harms are largely determined by both demand and supply of alcohol. Across Western Australia, under state licensing laws, there are state-wide alcohol sales restrictions imposed on Good Friday and Christmas Day each year. This study aimed to evaluate the effect of the Good Friday and Christmas Day state-wide alcohol restrictions on the risk of alcohol-related injuries presenting at emergency departments. METHODS: This is a population-based cohort study using ED injury presentation data for the period 1st January 2002 to 1st January 2015. Risk of injury during the alcohol-related time of day affected by the alcohol restrictions (intervention periods, including Good Friday and Christmas Day) were compared to the same time of day over a number of control days. Multivariable Poisson regression model was used to perform the analysis. RESULTS: The crude injury risk was considerably lower during the alcohol restriction periods compared to control periods in both metropolitan and non-metropolitan areas. The protective effect observed on the days of the alcohol restrictions remained significant, and largely unchanged, when potential confounding effects were controlled for. CONCLUSION: The significant reduction in alcohol-related injury presentations observed for public holiday periods with alcohol restrictions were likely caused by the alcohol restriction policy and its direct effect on alcohol supply.